Stringent Response Regulates Stress Resistance in Cyanobacterium Microcystis aeruginosa - Jin, Hui; Lao, Yong Min; Ying, Ke Zhen; Zhou, Jin; Cai, Zhong Hua (Frontiers in Microbiology, 2020)
Cyanobacterial blooms are serious environmental issues in global freshwater ecosystem. Nitrogen limitation is one of the most important strategies to control cyanobacterial blooms. However, recent researches showed that N limitation does not effectively control the bloom, oppositely, N limitation induces N-fixing cyanobacterial blooms. The mechanism underlying this ecological event is elusive. In this study, we found that N limitation enhances stress tolerance of Microcystis aeruginosa by triggering stringent response (SR), one of the most important bacterial adaptive responses to environmental stresses. Initiation of SR exerted protective effects on the cells against salt and oxidative stresses by promoting colony formation, maintaining membrane integrity, increasing photosynthetic performance, reducing ROS production, and upregulating stress-related genes, etc. These protections possibly help M. aeruginosa maintain population number during seasonal N limitation. As SR has been proven to be involved in nitrogen fixing under N limitation condition, the potential role of SR in driving the shift and succession of cyanobacterial blooms was discussed. Our findings provide cellular evidence and possible mechanism that reducing N input is ineffective for bloom control.